(untitled) (Research, Society and Development, 2020)
Introduction: mothers usually express doubts about the newborn’s bath and seek information in the information technologies. Therefore, it is questioned: How is the newborn bath content expressed in YouTube videos? Objective: to analyze the content of YouTube videos about bathing the newborn and discuss it with the scientific literature. Methodology: a study supported by the method of analysis of moving images whose collection was carried out on the YouTube website with the keyword “newborn bath” and time cut from 2016-2018. 61 videos were found and evaluated. Results: neutral liquid soap, location, water temperature and quantity, frequency and duration of the bath were the main recommendations of the videos. Conclusion: given the inconsistencies of the recommendations, it is necessary that prenatal care and accommodation are used as a space for health education with a demonstration of the bathing technique and necessary care to prevent risks and discomfort for the newborn.